The impact of the six-week program of proprioceptive training on the incidence of injuries in the RG - Cesar, I.; Vuckovic, G.; Cesar, P.; Ksenija, N. I.; Samardžija, P. M. (International Scientific Congress Slovenian Gymnastics Federation, 2017)
The study was aimed at the impact of the proprioceptive training on the athlete and at determining, by using equilibrium tests, whether there are differences in the balance indicators after performing the selected preventive exercise and thereby reduce the risk of injury. The study included nine top rhythmic gymnasts aged 16 ± 4.33 years. We used the test of 30 seconds of one leg stand with eyes open on the force plate. We measured the initial state, and after the six-week programme of preventive exercise, also the final state. The analysis of the results was done by using descriptive statistics for each parameter separately. The analysis of the differences at the level of individual contestants was checked with t-test for dependent samples. We observed four indicators: the path drawn by the projection of the pressure centre on the ground (CoP), the average path drawn by CoP to the ground, the oscillation frequency CoP to the ground and the index of fatigue. We observed all indicators in the direction forwards- backwards (A-P) and in the direction left - right (M-L). Regarding the average of the initial and final state two indicators showed statistically significant difference and an improved final state. For the indicator of the total path CoP to the ground in the direction forwards - backwards (AP) the significance has been 0.000 at p <0.05 (confidence interval of 1625.18 ± 764.93), for the indicator of the total path of CoP to the ground in the direction left - right (ML) the significance has been 0.027 at p <0.05 (confidence interval of 1850.67 ± 2059.56), for the indicator of the oscillation frequency of CoP to the ground in the direction forwards - backwards (AP) the significance has been 0.000, with p <0.05 (confidence interval 27.81 ± 2.58) and for the oscillation frequency of CoP on the ground in the direction left - right (ML) the significance has been measured at 0.001, at p <0.05 (confidence interval of 20.74 ± 12.17). For the indicators of average path drawn by the CoP to the ground and for the index of fatigue there were no statistically significant differences measured. By measuring equilibrium, we found that the program of proprioceptive preventive exercise had a positive impact on the ability to maintain balance. Through exercise we influenced the improvement of the body control and thereby reduced the risk of injury.